Use of extracorporeal shockwave therapy combined with standard rehabilitation following anterior cruciate ligament reconstruction: a systematic review with meta-analysis - Jaehyung Shin; Hye Chang Rhim; James Kim; Raymond Guo; Ramy Elshafey; Ki-Mo Jang (BMC Musculoskeletal Disorders)
Abstract Background Anterior cruciate ligament (ACL) injuries are one of the most common sports injuries, accounting for approximately 50% of knee-related injuries. Extracorporeal shockwave therapy (ESWT), in the form of the radial (R-SWT) or focused shockwave (F-SWT), has been shown effective in treating various orthopaedic conditions. Recently, studies have investigated whether ESWT combined with standard rehabilitation may improve outcomes following anterior cruciate ligament reconstruction (ACLR). Therefore, this study aimed to determine whether ESWT can improve clinical outcomes following ACLR. Methods This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). We searched PubMed, Embase, and Web of Science and included studies involving ESWT treatment following ACLR, which consisted of randomized controlled trials (RCTs) and cohort studies. Two authors independently extracted the outcome measurements and used a revised Cochrane risk-of-bias tool (RoB 2) for RCTs and the Risk of Bias in Non-randomised Studies of Interventions (ROBINS-I) for a cohort study to assess the risk of bias. A random effects pairwise meta-analysis was used to compare patient-reported outcomes between ESWT and controlled treatments. Results Five studies (Level I: 4; Level II: 1) with 242 participants (male: 167; female: 75) were included. Regarding the patient-reported outcomes, the risk of bias for all RCTs was ‘high’ and ‘serious’ for a non-randomized study. The meta-analysis demonstrated that the Lysholm scores were significantly higher in ESWT groups than those of controls at 12 months (Weighted mean difference [WMD]: 7.037, 95% confidence interval [CI]: 6.172–7.902, I2: 0%) and 24 months (WMD: 5.463, 95% CI: 2.870–8.056, I2: 0%). Furthermore, the International Knee Documentation Committee (IKDC) scores were also significantly higher in the ESWT group than that of the control at 12 months (WMD: 6.371, 95% CI: 3.397–9.344, I2: 68.8%). However, the WMDs for these outcomes between the two groups did not exceed the minimal clinically important difference (MCID). Conclusion Based on the meta-analyses performed with a few studies, ESWT combined with standard rehabilitation may potentially lead to better patient-reported outcomes. However, these differences may not be clinically significant. Further high-quality studies are needed to confirm our review’s findings.